Understanding the consecrated life in Canada: critical essays on contemporary trends - Zuidema, Jason (Studies in religion / Editions SR, 2015)
"In four parts, this book presents essays in both English and French from the leading scholars on religious life in Canada that seek to address the state of religious communities dedicated to religious virtuosity normally characterized by formal promises of chastity, poverty, and obedience. The essays examine a broad range of topics related to the general state of consecrated (or "religious" or "monastic") life in contemporary Canadian Christian and Buddhist traditions."--